Test Cases Minimization Strategy Based On Flower Pollination Algorithm - Ho, Chai Har; Al-Sewari, Abdul Rahman Ahmed Mohammed (2016)
The phenomenon of exhaustive testing in software testing is hard to implement due to a huge number of test cases and time-consuming in order to find bugs. Hence, a test cases minimization strategy is an essential to obtain an optimize test cases and consequently, time will also be reducing. An adoption of optimization based t-way strategies and nonoptimization based t-way strategies have come across. This paper describes the adoption of Flower Pollination Algorithm (FPA) in order to minimize the test cases. The FPA inspired from the reproduction of flowers to find the best optimum results when compared to other methods. This strategy will be evaluated by several published benchmarking.